Controversy: supporting patellar resurfacing in total knee arthroplasty – do it. Issue 11 (November 2020) - Benazzo, Francesco; Perticarini, Loris; Jannelli, Eugenio; Ivone, Alessandro; Ghiara, Matteo; Rossi, Stefano Marco Paolo
Abstract : Patellar resurfacing during total knee arthroplasty remains a controversial topic. Some surgeons routinely resurface the patella to avoid the increased rates of postoperative anterior knee pain and reoperation for secondary resurfacing, whilst others selectively resurface based on the presence of preoperative anterior knee pain, damaged articular cartilage, inflammatory arthritis, isolated patellofemoral arthritis, and patellar subluxation and/or maltracking. A third group of surgeons never resurface the patella. The anatomy and biomechanics of the patellofemoral joint as well as the advances in surgical techniques and prosthetic design must be taken into account when making a decision about whether to resurface the patella. Accurate component implantation if the patella is resurfaced becomes crucial to avoid complications. In our institution before 2008 we were performing a selective resurfacing of the patella, but in the last decade we have decided to always resurface it, with good outcomes and low complication rate. A reproducible surgical technique may be helpful in reducing the risk of postoperative anterior knee pain and complications related to implants. In this article we analyse the current trend and controversial topics in dealing with the patella in total knee arthroplasty, and discuss the available literature in order to sustain our choice. Cite this article: EFORT Open Rev 2020;5:785-792. DOI: 10.1302/2058-5241.5.190075